Insurance Policy Closure As The Implication of The Utmost Good Faith Principle in Life Insurance Claim Filing - Sianipar, Jessica Petra N; Cahyono, Akhmad Budi (Faculty of Law, Universitas Jenderal Soedirman, 2022)
The risk transfer mechanism from the insured to the insurer in insurance happens when both parties have fulfilled what has been agreed in insurance agreement along with obligatory insurance principle like the utmost good faith principle and the regulation regarding the insurance procedure. In the South Jakarta District Court Decision number: 16/Pdt.G/2016/PN.Jkt.Sel, Panel of Judges excluded what has been agreed by both parties on the basis of fulfillment of utmost good faith principle by the plaintiff. The excluded matter was regarding the written notification obligation that has been agreed by both parties, but the plaintiff did not notify it in writing but orally instead. Law No. 40 of 2014 does not clearly regulate claim notification, thus causing difficulty in determining whether certain notification is the application of the utmost good faith principle or not. Some foreign legislations regulate that matter, so they can become a reference for Indonesian regulators in perfecting the existing regulation.Keywords: insurance; the principle of utmost good faith; insurance policy closure; insurance claim; life insurance